System Design Early Detection of Teacher Burnout Based on Islamic Counseling in the Environment Islamic boarding school - Asep Rohani; Mar'atus Salamah; Hidayatul Faridah; Feri Hardiyanto (Indonesian Journal of Multidisciplinary Science, 2026)
Teacher burnout has become a critical issue in contemporary educational systems, particularly within Islamic boarding schools (Islamic boarding schools ) where teachers hold multidimensional responsibilities as educators, spiritual mentors, and social role models. However, studies on teacher burnout in Islamic boarding school contexts remain limited, especially those integrating Islamic counseling and workplace spirituality perspectives. This study aims to analyze the conditions and determinants of teacher burnout in Islamic boarding schools and to develop an Islamic counseling-based early detection model for teacher burnout prevention. This research employed a Sequential Exploratory Mixed Method design. The qualitative phase involved in-depth interviews, observations, and Focus Group Discussions (FGD) with pesantren teachers, school leaders, Islamic counselors, and senior students to explore burnout symptoms, causal factors, and teacher wellbeing needs. The quantitative phase involved 126 Islamic boarding school teachers and utilized burnout scales, spiritual wellbeing scales, and workplace spirituality scales to validate indicators and examine the effectiveness of the proposed system. The findings revealed that emotional exhaustion, spiritual stress, administrative workload, and organizational pressure were the dominant factors contributing to teacher burnout in Islamic boarding school environments. More than half of the participants experienced moderate to high levels of burnout, particularly in the dimensions of emotional exhaustion and workplace stress. The study also found that workplace spirituality contributed positively to teachers' psychological resilience;